2020
DOI: 10.1111/iji.12491
|View full text |Cite
|
Sign up to set email alerts
|

Association of BTLA rs1982809 polymorphism with lung cancer risk in Tunisian population

Abstract: B and T lymphocyte attenuator (BTLA) is an immune‐inhibitory receptor that negatively regulates the lymphocyte activation. A few studies have been devoted to the relationship between BTLA gene variations and cancer's risk. It has been essentially demonstrated to be involved in increasing cancer risk in chronic lymphocyte leukaemia, renal cell carcinoma, breast and colorectal cancer predispositions in Asian population. The aim of this study was to evaluate the association between BTLA gene polymorphisms and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…Fu et al revealed that BTLA gene polymorphisms were connected to the intensi ed risk of BC in Chinese women [24]. Nevertheless, they did not investigate rs1982809 polymorphism [24]. Honestly, this was the rst Chinese study to observe this nding.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Fu et al revealed that BTLA gene polymorphisms were connected to the intensi ed risk of BC in Chinese women [24]. Nevertheless, they did not investigate rs1982809 polymorphism [24]. Honestly, this was the rst Chinese study to observe this nding.…”
Section: Discussionmentioning
confidence: 91%
“…However, we observed that BTLA rs1982809 polymorphism elevated the risk of BC in Chinese women in this study. Fu et al revealed that BTLA gene polymorphisms were connected to the intensi ed risk of BC in Chinese women [24]. Nevertheless, they did not investigate rs1982809 polymorphism [24].…”
Section: Discussionmentioning
confidence: 99%
“…The association of the following genetic variants of BTLA rs1982809A>G , rs9288952A>G and rs9288953C>T with lung cancer risk was studied recently in the Tunisian population (196 patients, 300 controls) ( 220 ). The possession of rs1982809*G allele was associated with 1.5 increased risk of lung cancer development.…”
Section: B- and T-lymphocyte Attenuatormentioning
confidence: 99%
“…The possession of rs1982809*G allele was associated with 1.5 increased risk of lung cancer development. The rs1982809*G allele was also associated with T4 tumor size (OR = 1.8), metastasis to LNs (OR = 3.71), and development of adenocarcinoma subtype of lung cancer (OR = 2.8) ( 220 ). The summary of above-described associations between BTLA polymorphisms and cancer risk is shown in Supplementary Table 4 .…”
Section: B- and T-lymphocyte Attenuatormentioning
confidence: 99%
“…The BTLA gene is located on the chromosome 3q13.2. Previous studies have investigated whether BTLA rs1982809 polymorphism was linked with the risk of cancer, including renal cell carcinoma [20], chronic lymphocytic leukemia [21], esophagogastric junction adenocarcinoma [22], esophageal squamous cell carcinoma [23] and lung cancer [24]. However, no studies explored the association of this polymorphism and BC risk.…”
Section: Introductionmentioning
confidence: 99%